Regulation of (pro)renin receptor expression in mIMCD via the GSK-3β-NFAT5-SIRT-1 signaling pathway - Quadri, Syed (Am J Physiol Renal Physiol, 2014)
The localization and regulation of (pro)renin receptor (PRR) expression in kidney collecting duct cells are not well established. We hypothesized that low salt (LS) contributes to the regulation of PRR expression in these cells via the GSK-3β-NFAT5-sirtuin1 (SIRT-1) signaling pathway. Mouse inner medullary collecting duct (mIMCD) cells were treated with NaCl at 130 (normal salt; NS), 63 (LS), or 209 mM (high salt; HS) alone or in combination with NFAT5 scrambled small interfering (si) RNA, NFAT5 siRNA, or the SIRT-1 inhibitor EX-527. Compared with NS, LS increased the mRNA and protein expression of PRR by 71% and 69% (P < 0.05), and reduced phosphorylation of GSK-3β by 62% (P < 0.01), mRNA and protein expressions of NFAT5 by 65% and 45% (P < 0.05), and SIRT-1 by 44% and 50% (P < 0.01), respectively. LS also enhanced p65 NF-κB by 102% (P < 0.01). Treatment with HS significantly reduced the mRNA and protein expression of PRR by 32% and 23% (P < 0.05), and increased the mRNA and protein expression of NFAT5 by 39% and 45% (P < 0.05) and SIRT-1 by 51% and 56% (P < 0.05), respectively. HS+NFAT5 siRNA reduced the mRNA and protein expression of NFAT5 by 51% and 35% (P < 0.01) and increased the mRNA and protein expression of PRR by 148% and 70% (P < 0.01), respectively. HS+EX-527 significantly increased the mRNA and protein expression of PRR by 96% and 58% (P < 0.05), respectively. We conclude that expression of PRR in mIMCD cells is regulated by the GSK-3β-NFAT5- SIRT-1 signaling pathway.